THE INFLUENCE OF CONCENTRATION LIQUID WASTE OF TOFU PRODUCTION TO DAPHNIA SP CULTIVATION BIOMASS - Mujtahidah, Tholibah; Kusuma, Baruna (University of Muhammadiyah Malang)
A natural feed of freshwater fish as long as it depends on worms tubifex is hard to be cultivated. Daphnia sp is one of the kinds of Cladocera zooplankton to be an alternative as a natural feed for seed of fish. The liquid tofu waste generally is a problem that is going on in every regional particularly around the Kedu Residency, Central Java. The liquid waste has the nutritional value that can be used for cultivation Daphnia sp. The right concentration of liquid waste tofu to the cultivation of Daphnia sp. has not been studied. This research aimed to find out the influence of concentration out over the density of waste biomass and the visibility of morphology Daphnia sp. The experiment used Complete Randomized Design (CRD) with three treatments and three repetitions, 25:75, 50:50, dan 75:100 (TI, T2, and T3, respectively), tofu liquid waste and water. The results concluded that T3 has repercussions for the density and biomass Daphnia sp. The density of Daphnia sp. was shown by treating 75 % of liquid tofu waste with 31.33 ind L-1 on average and while biomass was 4.6 g L-1 on average. The visibility of Daphnia sp morphology was cultivated with liquid tofu waste compared with Daphnia sp. cultivated using wastewater of catfish cultivation as a control group.Keywords: Biomass, Daphnia sp., Liquid tofu waste, Present of morphology